2010
DOI: 10.1186/1476-4598-9-182
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB activation enhances cell death by antimitotic drugs in human prostate cancer cells

Abstract: BackgroundNF-κB is a transcription factor that promotes inhibition of apoptosis and resistance to chemotherapy. It is commonly believed that inhibition of NF-κB activity can increase sensitivity of cancer cells to chemotherapy. However, there is evidence that NF-κB activation can sensitize cells to apoptosis and that inhibition of NF-κB results in resistance to chemotherapy. In prostate cancer, it is not clear in the different cell types (androgen-dependent and castration-resistant) if activation or inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 53 publications
1
47
0
1
Order By: Relevance
“…S6). Our DUB assay results showed that BA treatment of LNCaP cells reduced DUB activity starting at 24 h. In contrast, treatment of LNCaP with 1 nM docetaxel, a dose that increased apoptotic cell death [28], had less effect on DUB activity (Fig. 6B).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…S6). Our DUB assay results showed that BA treatment of LNCaP cells reduced DUB activity starting at 24 h. In contrast, treatment of LNCaP with 1 nM docetaxel, a dose that increased apoptotic cell death [28], had less effect on DUB activity (Fig. 6B).…”
Section: Resultsmentioning
confidence: 81%
“…1) as an agent that can enhance the sensitivity of PC cell lines to cell death when combined with antimitotic agents by increasing NF-κB activity, in part due to enhanced degradation of IκBα [27], [28]. To evaluate the in vivo therapeutic efficacy of BA, we utilized the TRAMP transgenic mouse model of PC [29], [30].…”
Section: Resultsmentioning
confidence: 99%
“…The NF-κB luciferase reporter construct (NF-κB-Luc) containing four copies of NF-κB cis-acting elements linked to TATA box was cloned into pGL3 basic vector [24]. Cells were plated in 24-well plates, then the cells were co-transfected with NF-κB-Luc plasmid and the internal control plasmid renilla luciferase (pRL-TK) using transfection reagent Lipofectamine 2000 (Invitrogen, Carlsbad, CA) as described previously [25].…”
Section: Methodsmentioning
confidence: 99%
“…Even though activation of NF‐κB signalling is involved in some cell pro‐survival pathways, it is also implicated under some conditions in apoptotic induction . Several oncolytic viruses, such as reoviruses and Newcastle disease virus, have been reported to require activation of the NF‐κB signalling pathway for their induction of apoptosis in cancer cells .…”
Section: Discussionmentioning
confidence: 99%